The Expression of Tax and HBZ Genes in Serum-Derived Extracellular Vesicles From HTLV-1 Carriers Correlates to Proviral Load and Inflammatory Markers - de La-Roque, Debora Glenda Lima; Santos, Elaine Vieira; Rodrigues, Evandra Strazza; da Costa, Péricles Natan Mendes; Brauer, Verônica Soares; Almeida, Fausto; de Haes, Tissiana Marques; Takayanagui, Osvaldo Massaiti; Covas, Dimas Tadeu; Kashima, Simone (Frontiers in Microbiology, 2022)
Human T-lymphotropic virus 1 (HTLV-1) is the etiologic agent of adult cell leukemia/lymphoma (ATL) and HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP). One of the major questions in HTLV-1 studies is related to the understanding of causes that lead to different clinical manifestations. However, it is well known that the viral genes tax and HTLV-1 basic leucine zipper factor (HBZ) are related to viral infectivity and the development of neurological and hematological diseases. Currently, there is evidence that HTLV-1 infected cells can release small extracellular vesicles (sEV) involved in mechanisms of viral particles spreading. Therefore, we evaluated the expression levels of tax and HBZ viral transcripts in serum-derived sEV from HTLV-1 carriers, as well as the role of these vesicles in the modulation of the immune response. Three HAM/TSP carriers presented detectable levels of tax and HBZ transcripts in sEV and were positively correlated to the PVL in peripheral blood mononuclear cells (PBMC). The viral transcripts were only detectable in individuals with PVL higher than 6,000/10^5 PBMC. It was also observed that HBZ presented a 2 to 12 fold increase over tax expression units. Gene expression and secretory protein analysis indicated that PBMC from blood donors and HTLV-1 carriers exposed to increasing doses of tax+ HBZ+ sEV showed a dose-dependent increase in IFN-γ and IL-8 transcripts and proteins. Interestingly, the increase in IL-8 levels were close to those seen in HTLV-1-infected PBMC with high PVL. Taken together, these findings indicate that the expression of viral transcripts in serum- derived sEV of HTLV-1 carriers is related to the PVL presented by the infected individual. Additionally, tax+ HBZ+ sEV can induce the production of inflammatory cytokines in patients with low PVL, which may be related to the development of symptoms in HTLV-1 infection.